Z węgierskiej perspektywy. Olga Tokarczuk. Z Lajosem Pálfalvim rozmawia Sandra Trela - Pálfalvi, Lajos; Trela, Sandra (Postscriptum Polonistyczne, 2020)
In the interview, Professor Lajos Pálfalvi, an outstanding translator of Polish literature into Hungarian and the head of the Department of Polish Studies at the Pázmány Péter Catholic University in Budapest, presents the story of his contacts with Olga Tokarczuk, starting from the 1990s when he met her personally as a promising novice. He gladly shares his vivid recollections and anecdotes related not only to the Polish Nobel Prize winner, but also to Hungarian and Polish literary life in the recent decades. He also talks about translation methodology and shares observations on the interpretation of Tokarczuk’s work.